2017
DOI: 10.1016/j.obhdp.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Spillover bias in diversity judgment

Abstract: Diversity research has long assumed that individuals' perceptions of diversity are accurate, consistent with normative theories of judgments in economics and decision theory. We challenge this assumption. In six experiments, we show that when there is more diversity along one dimension (e.g., race, clothing color), people also perceive more diversity on other dimensions (e.g., gender, skill) even when this cannot reflect reality. This spillover bias in diversity judgment leads to predictable errors in decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…Oosthuizen et al [ 63 ] also indicated the tendency among males to feel discriminated against by female competitors whenever AA is implemented. Such findings reinforce the idea that affirmative action—particularly gender AA—can be perceived differently by individuals of different genders [ 68 ]. Figure 1 illustrates the full path model developed in this paper, comprising the topics discussed by the authors, and mapping the relationship between antecedents and outcomes of AA in management.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Oosthuizen et al [ 63 ] also indicated the tendency among males to feel discriminated against by female competitors whenever AA is implemented. Such findings reinforce the idea that affirmative action—particularly gender AA—can be perceived differently by individuals of different genders [ 68 ]. Figure 1 illustrates the full path model developed in this paper, comprising the topics discussed by the authors, and mapping the relationship between antecedents and outcomes of AA in management.…”
Section: Resultssupporting
confidence: 84%
“…Despite diverging on the conceptual definition of AA, EEO and DM (and the relationships among them), there is a noteworthy commonality among authors supporting prior experiences with one or all the aforementioned initiatives [ 22 , 23 , 66 , 68 ] as anteceding general perceptions [ 33 , 67 , 69 , 70 , 71 ] and attitudes towards them. More importantly, by considering the different initiatives as intertwined and connected to each other, scholars also pointed out the misunderstanding regarding the boundaries between the three as well as a spillover on the purpose or effect of each of them [ 23 , 28 , 29 , 31 , 33 , 34 , 47 , 68 ]. More recently, authors have agreed that it is precisely such blurred ideas on AA that may lead to misjudgment and rejection among individuals, particularly those that might feel threatened by such initiatives [ 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…While this line of work is encouraging, one of the key challenges is that perceptions of group diversity are not always accurate, and may have little to do with the objective levels of group diversity. Other aspects of team composition (Daniels et al 2017) as well as the normative context (Chatman et al 1998) can influence how accurately members' perceive their group's objective diversity. If perceptions of diversity can determine team outcomes more reliably than objective measures, the lack of a theoretical framework to understand how team norms and objective diversity levels interact to predict perceived group diversity (and, thereby, group outcomes) is problematic.…”
Section: Collectivism and Perceived Group Diversitymentioning
confidence: 99%
“…Of those who were inaccurate, only 3% perceived there to be more national diversity than actually existed and 5% perceived there to be more expertness diversity than actually existed, suggesting that inaccuracy was almost always in the direction of seeing less diversity than what actually existed in the group. We then averaged individual accuracy at the group level, with scores ranging from 0 (no members correctly perceived their group composition) to 1 (all three members correctly perceived their group composition), and similar to past approaches (Daniels et al 2017) we used two (accuracy of) perceived group diversity scores -one each for national diversity and expertness diversity.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…We focus on salient demographic characteristics because, as Tsui, Egan and Porter (1994) note, these "physical, observable, and immutable personal and background characteristics….play a critical role in the initial categorization process" (as cited in Harrison, Price, & Bell, 1998) and thus would affect satisfaction/frustration of identity motives. We focus on ethnic dissimilarity, in particular, because group members commonly categorize one another into ethnic categories based on observable surface-level differences early in group life, and ethnicity is a prototypical attribute of "diversity" (Daniels, Neale, & Greer, 2017;Mannix & Neale, 2005). Ethnic categorizations in daily social interaction are fluid and informal (Jenkins, 1994;Okamura, 1981) and are based on contextual similarities and differences in observable (e.g., visible or audible) characteristics such as skin color or use of language Our paper has two goals: First, we examine how ethnic dissimilarity affects members' needs for distinctiveness and belonging.…”
mentioning
confidence: 99%